Comparison of uterine, endometrial and subendometrial blood flows in predicting pregnancy outcomes between fresh and frozen-thawed embryo transfer after GnRH antagonist protocol: a retrospective cohort study - Jianmei Yu; Bo Li; Haiyan Li; Qing Li; Zhen Nai; Bo Deng; Yunxiu Li (Taylor & Francis Group, 2023)
This retrospective cohort study aimed to compare endometrial receptivity and pregnancy rate between fresh embryo transfer (ET) and frozen-thawed ET after gonadotrophin-releasing hormone (GnRH) antagonist protocol in normal ovarian responders. The patients were divided into two groups: the fresh ET group and the frozen-thawed ET group. Uterine artery resistance index (RI) and endometrial thickness were lower in the frozen-thawed ET group. The proportion of detectable endometrial-subendometrial flow was significantly higher in the frozen-thawed ET group. There was no significant difference in miscarriage rate between the two groups. Frozen-thawed ET group had a significantly higher CPR (56.0% vs. 48.1%), implantation rate (32.2% vs. 26.4%), and LBR (45.4% vs. 36.5%) than the fresh ET group. In GnRH antagonist protocol, elective frozen-thawed ET should be ideally taken, as this could improve embryo implantation rate, clinical pregnancy rate, and live birth rate, thus presenting an effective strategy to enhance the embryo utilization rate.IMPACT STATEMENT What is already known on this subject? The clinical pregnancy rate following fresh embryo transfer (ET) was lower than frozen-thawed ET after GnRH antagonist protocol. IVF success depends on embryo quality, embryo-endometrium interaction and endometrial receptivity. A good blood supply toward the endometrium is generally considered a requirement for implantation. What do the results of this study add? Uterine artery RI and endometrial thickness were significantly lower in the frozen-thawed ET group. The proportion of detectable endometrial-subendometrial flow was significantly higher in the frozen-thawed ET group. Frozen-thawed ET group had a significantly higher clinical pregnancy rate, implantation rate and live birth rate than the fresh ET group after GnRH antagonist protocol. What are the implications of these findings for clinical practice and/or further research? In GnRH antagonist protocol, elective frozen-thawed ET should be ideally taken, as this could improve embryo implantation rate, clinical pregnancy rate and live birth rate, thus presenting an effective strategy to enhance the embryo utilization rate.